2011
DOI: 10.1177/1947601911407329
|View full text |Cite
|
Sign up to set email alerts
|

The RalGEF-Ral Effector Signaling Network: The Road Less Traveled for Anti-Ras Drug Discovery

Abstract: The high frequency of RAS mutations in human cancers (33%) has stimulated intense interest in the development of anti-Ras inhibitors for cancer therapy. Currently, the major focus of these efforts is centered on inhibitors of components involved in Ras downstream effector signaling. In particular, more than 40 inhibitors of the Raf-MEK-ERK mitogen-activated protein kinase cascade and phosphoinositide 3-kinase-AKT-mTOR effector signaling networks are currently under clinical evaluation. However, these efforts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
116
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 139 publications
(154 reference statements)
0
116
0
Order By: Relevance
“…It has been shown that oncogenic Ras activates RalGEFs, which in turn activate the Ras-like small GTPases RalA and RalB (Lim et al, 2005;Urano et al, 1996;White et al, 1996;Wolthuis et al, 1998). Moreover, RalGEF-Ral signaling stimulates gene expression (Neel et al, 2011). It is therefore likely that Ral mediates the observed increased levels of exocyst proteins in Ras V12 cells.…”
Section: Oncogenic Ras Stimulates Eiger/tnf Exocytosismentioning
confidence: 91%
See 1 more Smart Citation
“…It has been shown that oncogenic Ras activates RalGEFs, which in turn activate the Ras-like small GTPases RalA and RalB (Lim et al, 2005;Urano et al, 1996;White et al, 1996;Wolthuis et al, 1998). Moreover, RalGEF-Ral signaling stimulates gene expression (Neel et al, 2011). It is therefore likely that Ral mediates the observed increased levels of exocyst proteins in Ras V12 cells.…”
Section: Oncogenic Ras Stimulates Eiger/tnf Exocytosismentioning
confidence: 91%
“…Indeed, the fact that blocking exocytosis of Eiger/TNF can suppress oncogenic Ras-mediated growth highlights the importance of Eiger/TNF exocytosis in cancer biology. Exocytosis proteins are conserved and have been implicated in diverse human cancers types, including Ras cancers (Cheng et al 2004(Cheng et al , 2005Issaq et al, 2010;Neel et al, 2011;Palmer et al, 2002), suggesting that a similar tumor-promoting mechanism could be at play in vertebrates. Because sec15 null mutation does not cause cell lethality and the gene is evolutionarily conserved, it suggests a new type of potential therapeutic targets.…”
Section: Oncogenic Ras Stimulates Eiger/tnf Exocytosismentioning
confidence: 99%
“…A second important group of effectors is the class IA catalytic subunits of phosphoinositide 3-kinases (PI3Ks). The third-best validated class of effectors required for Ras-mediated oncogenesis is comprised of guanine nucleotide exchange factors (RalGEFs) for the highly related RalA and RalB small GTPases (7,51). In PDAC, our studies suggest that the RalGEF-Ral effector pathway may be more essential than Raf or PI3K signaling for mutant KRAS-dependent tumor growth (34).…”
mentioning
confidence: 89%
“…There is increasing evidence for the importance of the RalA and RalB small GTPases in mutant Ras-driven oncogenesis (4, 5). RNAi knockdown of endogenous RalA in PDAC cells significantly impaired anchorage-independent growth whereas knockdown of RalB impaired Matrigel invasion in vitro and experimental metastasis in vivo (6).…”
Section: Introductionmentioning
confidence: 99%